Sosialisasi dan Edukasi Visi Misi Hasil Musyawarah Pastoral IX Keuskupan Atambua di Dekenat Mena : Socialization and Education of the Vision and Mission of the IX Pastoral Conference of the Diocese of Atambua in the Mena Decenate - Asa Siri, Theodorus; Sesfao, Marianus (Jurnal Suara Pengabdian 45, 2024)
In September 2023, the Diocese of Atambua's 9th Pastoral Conference (Muspas) in Emmaus initiated a mission to redefine its pastoral vision to address current social challenges. Led by the Bishop, the quinquennial plan emphasizes enhancing understanding of Church teachings amidst socio-economic and human development concerns. Particularly in the Mena deanery of North Central Timor, a culturally diverse and pivotal area, STP St. Peter's efforts aimed to align pastoral agents with this renewed vision. The collaborative educational approach underscores the importance of education, economic prosperity, and synodal collaboration as church success cornerstones. This strategy fosters a uniform approach across the diocese, encouraging ecological farming initiatives for sustainable development, and dynamic evangelization. The ultimate goal is fostering a community that progresses in intelligence and prosperity, in harmony with the Church's evolving vision and mission.